1995
DOI: 10.1002/gepi.1370120109
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a recessive major gene for high IgE levels acting independently of specific response to allergens

Abstract: The genetic control of the total IgE, the immunoglobulins E involved in allergy, remains still unclear. Although high IgE levels were found to be determined by a recessive major gene in several studies, other modes of inheritance were also reported. Moreover, at least two different genetic mechanisms controlling the IgE regulation have been suggested: one involved in the specific IgE response and the other one in the nonspecific response. To better understand the genetic mechanisms controlling IgE variation, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 13 publications
5
36
0
Order By: Relevance
“…Using total IgE as a quantitative trait for genetic studies of atopy has produced widely conflicting results, particularly with regard to the proportions of the responses putatively attributed to inheritance [1][2][3][4][5][6][7][8][9][10]. Although controlled by tight metabolic regulation, the production of IgE involves multiple pathways [26][27][28], but the details of these interrelationships are not completely understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using total IgE as a quantitative trait for genetic studies of atopy has produced widely conflicting results, particularly with regard to the proportions of the responses putatively attributed to inheritance [1][2][3][4][5][6][7][8][9][10]. Although controlled by tight metabolic regulation, the production of IgE involves multiple pathways [26][27][28], but the details of these interrelationships are not completely understood.…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of total IgE as a quantitative trait for genetic studies of atopy has produced widely conflicting results, with evidence for co-dominant genetic effects [1], recessive effects [2][3][4], pleiotropic effects [5] and other modes of inheritance [6][7][8][9][10]. Further, it has not been clearly established that enhanced total IgE production is a predisposing cause for atopy, as it may only be a consequence that accompanies clinical conditions, so the physiological 'sources' of total IgE are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Previous segregation analyses on families do not agree on the model of inheritance. However, several studies have found evidence of recessive inheritance of high total serum IgE levels (51)(52)(53)(54). Martinez et al reported evidence of codominant inheritance in a large sample of families (55).…”
Section: Studies On Igementioning
confidence: 99%
“…Dizier et al (58) used the regressive models to better understand the genetic mechanisms controlling immunoglobulin E in allergy in 234 Australian nuclear families. Segregation analysis of immunoglobulin E levels taking into account specific response to allergens was performed.…”
Section: Family Study Design and Segregation Analysesmentioning
confidence: 99%